Web-based evaluation of experts' opinions on impacted maxillary canines forced eruption using CBCT - Miresmaeili,Amirfarhang (2015)
AIM: This study aims at examining the difficulty in performing forced eruption of impacted maxillary canines, using CBCT information and according to experienced orthodontist's opinion. The second aim was to find the most important factors related to this decision. METHODS: Based on a careful literature review on impacted maxillary canines, ten main factors were selected to assess difficulties associated with impacted teeth. Thirty six consecutive patients with 50 impacted maxillary canines were examined and variables were measured for each impacted tooth using Dolphin 3D software. Ten orthodontists assessed the radiographs of teeth and provided their opinion on the difficulty in bringing impacted teeth into occlusion named subjective degree of difficulty (SDD). The correlation established between mean SDD of each tooth and measured variables were analyzed by means of linear regression. RESULTS: Mean SDD was 6.45 ± 1.22 for all 50 teeth. Linear regression showed a high coefficient of correlation between mean SDD and age, dilacerations, vertical height, angulation and horizontal overlap (P < 0.05). CONCLUSION: To predict the difficulty of impacted maxillary canines forced eruption, according to the opinion of experienced orthodontists, the factors age, dilaceration, angulation, overlap and vertical distance from the occlusal plane are the most important variables.